WHY PROFESSION IS NOT IN ACCORDANCE WITH THE FIELD OF SCIENCE? - Yasminar A. Telaumbanua; Rita Kristiani Telaumbanua; Intan Hartini Ndruru; Sevtryani Harefa; Zun Kelvin Halawa; Jernita Gulo; Putrawan Saleh Laia (Program Studi Pendidikan Bahasa Inggris, 2024)
Education is something that greatly affects human life. Without education people would not be able to progress this far, therefore people choose to be highly educated to survive. However, so far we know that being highly educated will not always guarantee one's success. In this case, it leads to the fact that there are so many humans who have higher education but the profession they have is not in accordance with the field of knowledge they have, especially generation Z. This research discusses the causes of professions that are not in accordance with their fields of knowledge. The method used was a qualitative method with a phenomenological approach and interview instruments. In this study also the respondents were several generation Z. The purpose of this study, to find out about the causes of the profession not in accordance with the field of science. And the result is that there are several causes of the profession that is owned not in accordance with the field of science. One that is familiar is choosing the wrong major. Choosing the wrong major is the most common cause mentioned by the interviewees. However, there are still several other causes of professions not in accordance with the field of science.